Clinical Prehospital Interventions in Trauma Care: A Systematic Literature Review - Pipik Taufik; Apsara Anindyajati Widiardi; Yuriche Ughude; Elis Marvela; Stevani Clara Febriyani; Ridlwan Kamaluddin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Trauma remains a leading cause of mortality and disability worldwide, particularly among working-age individuals. A significant proportion of trauma deaths occur during the early post-injury period, underscoring the critical need for effective prehospital interventions. Various strategies including airway management, hemorrhage control, blood product resuscitation, oxygen therapy, and pharmacological treatments have been implemented, though their efficacy varies across studies. This study aims to identify and classify prehospital clinical interventions for trauma patients, assess the quality and strength of the evidence, and determine evidence gaps and their implications for clinical practice and trauma system policy. This systematic review adhered to PRISMA 2020 guidelines, searching in database Scopus (2020-2026) for studies on trauma patients receiving prehospital interventions (RCTs/cohort studies) reporting outcomes such as mortality, survival to discharge, hemodynamic stability, complications, or length of hospital stay. Methodological quality was assessed using Joanna Briggs Institute tools, with narrative synthesis due to study heterogeneity. Of 1,877 records, seven studies met inclusion criteria, primarily RCTs from high-income countries. Tranexamic acid (TXA) was most frequently studied, demonstrating reduced 28-day mortality and transfusion requirements without increased thromboembolic risk. Prehospital blood product resuscitation and oxygen therapy strategies yielded mixed or neutral findings. Prehospital TXA administration provides the most consistent survival benefit for bleeding trauma patients. Further high-quality research is needed to optimize other prehospital interventions and strengthen evidence-based trauma systems.